Islam as a challenge to the ideology of religious studies: Failures of religious studies in the Middle East - Henley, A (Equinox Publishing, 2020)
Why has Religious Studies failed to gain ground in Middle Eastern universities? This article aims to move beyond a lens of underdevelopment to think about the significance of Muslim opposition to the discipline. When we suppose that studying religion and religions is an obvious thing to do, we risk casting those who deliberately avoid it as somehow irrationally refusing to see what is in front of them. But what if their objections reveal something troubling about the received terms through which we talk about cultures around the world? By taking seriously a certain Islamic perspective on the terms of Western scholarship, this article highlights ways in which it supports Timothy Fitzgerald’s critique in The Ideology of Religious Studies (2000). It poses a challenge to the idea of value-free study of religion, religions and the religious as conducted through any discipline. This author’s hope is that a focus on Muslim voices may bring these concerns home in particular to the fields of Islamic and Middle Eastern Studies, where the terms of comparative Religious Studies have been embraced as an escape from Orientalism.